2009
DOI: 10.1039/b905718h
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of benzophenone with ammonium phosphomolybdate in the solid state via UV photoactivation

Abstract: UV photoactivation of a mixture of benzophenone and ammonium phosphomolybdate (APM) in the solid state splits adsorbed moisture, resulting in selectively hydroxylated benzophenone and leaving an electron trapped in green (reduced) solid APM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The nanocomposite developed for further usage in stereolithography application was prepared using benzophenone and TiO 2 nanoparticles, and consequently, the mixed material was irradiated with 360 nm UV radiation. The reason behind using UV radiation with this wavelength is the sensitivity of both benzophenone and nano-TiO 2 to radiations below 365 nm [20,21]. The UV spectra of the photoinitiator has absorption peaks at 258 nm [22,23], while the used photocatalyst filler (TiO 2 ) presents absorption peak at 336 nm, and a tail at 370 nm, as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The nanocomposite developed for further usage in stereolithography application was prepared using benzophenone and TiO 2 nanoparticles, and consequently, the mixed material was irradiated with 360 nm UV radiation. The reason behind using UV radiation with this wavelength is the sensitivity of both benzophenone and nano-TiO 2 to radiations below 365 nm [20,21]. The UV spectra of the photoinitiator has absorption peaks at 258 nm [22,23], while the used photocatalyst filler (TiO 2 ) presents absorption peak at 336 nm, and a tail at 370 nm, as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivity towards water is of special concern, because as part of the MOF framework, all the benzophenone moieties are exposed, and even air humidity might lead to a reaction under light exposure. Actually, there are only very few studies in the literature for the reaction of benzophenone moieties in aqueous media . For the studies of the photochemical reactivity towards water, we used the Zr‐ bzpdc ‐MOF and, for comparison, the free linker molecule H 2 bzpdc to obtain fundamental insights into possible differences in photoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…This part focusses on the reactions with simple molecules, namely methanol and ethanol as well as water. Only few studies have reported on the reactions of benzophenone in aqueous media; in the present case, these may be especially important, as in the laboratory the MOF samples are exposed to light and air humidity when no special precautions are taken. In the second part of the study, we have reacted the Zr‐ bzpdc ‐MOF with series of alkanes and alcohols of different chain length.…”
Section: Introductionmentioning
confidence: 99%
“…8 The backbone of the [PMo 12 O 40 ] 3À anion consists of a central tetrahedral [PO 4 ] À3 zone that provides strength to the molecule. [3][4][5][6][7][8][9] Recently APM has been proved to be an attractive catalyst, [10][11][12] a support material for drug delivery, 13 performs biological activities, 14 DNA synthesis and repair, 14,15 sustain photochemical reaction, [16][17][18] nanoparticle synthesis, 19 cathode active material, 20,21 and even electrochemical application. 22 Many of these applications originated from the redox activity of the [PMo 12 O 40 ] 3À anion with a robust electron reservoir capability.…”
Section: Introductionmentioning
confidence: 99%